Slow growth of Burkholderia pseudomallei compared to other pathogens in an adapted blood culture system in Phnom Penh, Cambodia. Issue 8 (12th June 2019) - Peeters, Marjan; Ombelet, Sien; Chung, Panha; Tsoumanis, Achilleas; Lim, Kruy; Long, Leng; De Smet, Birgit; Kham, Chun; Teav, Syna; Vlieghe, Erika; Phe, Thong; Jacobs, Jan
Abstract : Purpose. Burkholderia pseudomallei is a key pathogen causing bloodstream infections at Sihanouk Hospital Center of Hope, Phnom Penh, Cambodia. Here, visual instead of automated detection of growth of commercial blood culture bottles is done. The present study assessed the performance of this system. Methodology. Blood culture sets, consisting of paired adult aerobic and anaerobic bottles (bioMérieux, FA FAN 259791 and FN FAN 252793) were incubated in a standard incubator for 7 days after reception. Each day, the bottle growth indicator was visually inspected for colour change indicating growth. Blind subculture was performed from the aerobic bottle at day 3. Results. From 2010 to 2015, 11  671 sets representing 10  389 suspected bloodstream infection episodes were documented. In 1058 (10.2  %) episodes, pathogens grew; they comprised Escherichia coli (31.7 %), Salmonella Paratyphi A (13.9 %), B. pseudomallei (8.5 %), Staphylococcus aureus (7.8 %) and Klebsiella pneumoniae (7.0 %). Blind subculture yielded 72 (4.1  %) pathogens, mostly (55/72, 76.4 %) B. pseudomallei . Cumulative proportions of growth at day 2 were as follows: E. coli : 85.0 %, Salmonella Paratyphi A: 85.0 %, K. pneumoniae : 76.3  % and S. aureus : 52.2  %; for B. pseudomallei, this was only 4.0  %, which increased to 70.1  % (70/99) at day 4 mainly by detection on blind subculture (55/99). Compared to the anaerobic bottles, aerobic bottles had a higher yield and a shorter time-to-detection, particularly for B. pseudomallei . Conclusions. Visual inspection for growth of commercial blood culture bottles in a low-resource setting provided satisfactory yield and time-to-detection. However, B. pseudomallei grew slowly and was mainly detected by blind subculture. The aerobic bottle outperformed the anaerobic bottle.